Peran Balaghah Terhadap Penafsiran Ayat-Ayat Akhlak Dalam Al-Qur’an - Sidik, Anwar; Sari, Rizka (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Balaghah plays a vital role in understanding the beauty of the Qur’anic language, particularly in interpreting verses related to morality. Moral verses in the Qur’an are often conveyed through profound linguistic expressions, including word choice, sentence structure, and the use of rhetorical devices and symbolism. A deep understanding of balaghah enables interpreters (mufassirun) to uncover the moral meanings embedded in these verses. This study analyzes how elements of balaghah, such as majaz (figurative language), isti‘arah (metaphor), tasybih (simile), and kinayah (metonymy), contribute to comprehending the Qur’an’s moral messages. The study employs a qualitative-descriptive approach. The data sources consist of Qur’anic verses related to ethics and morality, collected through literature review. The data analysis technique used is conten analysis. The results reveal that the rhetorical style in moral verses serves to enhance the moral message and deepen the reader’s understanding. The use of balaghah in ethical verses does not only function to convey explicit commands and prohibitions but also fosters deeper moral awareness. The linguistic structures used in these verses possess aesthetic appeal that strengthens the reader's absorption of the moral values conveyed.